2016
DOI: 10.1103/physrevlett.116.052501
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Resonant Tetraneutron State Populated by theHe4(He8

Abstract: A candidate resonant tetraneutron state is found in the missing-mass spectrum obtained in the double-charge-exchange reaction ^{4}He(^{8}He,^{8}Be) at 186  MeV/u. The energy of the state is 0.83±0.65(stat)±1.25(syst)  MeV above the threshold of four-neutron decay with a significance level of 4.9σ. Utilizing the large positive Q value of the (^{8}He,^{8}Be) reaction, an almost recoilless condition of the four-neutron system was achieved so as to obtain a weakly interacting four-neutron system efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
128
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 32 publications
9
128
4
Order By: Relevance
“…In addition to the 6 He(p, 2p) 5 H reaction used by Korsheninnikov, Meister et al reported 3 H+2n correlations from proton-knockout data from 6 He on a 12 C target [24], and gave a resonance energy E R =2.5-3.0 MeV and width Γ=3-4 MeV, rather different from earlier results. Another proton-removal reaction that could be used to search for 5 H is 6 He(d, 3 He) 5 H. Some reports of this reaction [25][26][27] exist.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…In addition to the 6 He(p, 2p) 5 H reaction used by Korsheninnikov, Meister et al reported 3 H+2n correlations from proton-knockout data from 6 He on a 12 C target [24], and gave a resonance energy E R =2.5-3.0 MeV and width Γ=3-4 MeV, rather different from earlier results. Another proton-removal reaction that could be used to search for 5 H is 6 He(d, 3 He) 5 H. Some reports of this reaction [25][26][27] exist.…”
Section: Introductionmentioning
confidence: 59%
“…Suggestions of correlated "dineutron" emission have recently been reported [1][2][3]. Experimental reports supporting the observation of the tetra-neutron have also appeared [4,5]. Some theoretical analyses indicate that it should not be stable or quasi-stable [6,7], although a recent report of No Core Shell Model (NCSM) calculations for 4 n suggests the possibility of a broad, low-lying resonance [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations